A stellar over-density associated with the Small Magellanic Cloud - Pieres, Adriano; Martínez-Delgado, David (Arxiv, 2017)
We report the discovery of a stellar over-density 8$^{°}$ north of the center of the Small Magellanic Cloud (Small Magellanic Cloud Northern Over-Density; SMCNOD) using data from the first two years of the Dark Energy Survey (DES) and the first year of the MAGellanic SatelLITEs Survey (MagLiteS). The SMCNOD is indistinguishable in age, metallicity and distance from the nearby SMC stars, being primarly composed of intermediate-age stars (6 Gyr, Z=0.001), with a small fraction of young stars (1 Gyr, Z=0.01). The SMCNOD has an elongated shape with an ellipticity of 0.6 and a size of $\sim$ 6x2 deg. It has an absolute magnitude of $M_V \cong$ -7.7, $r_h = 2.1$ kpc, and $μ_V(r<r_h)$ = 31.2 mag arcsec$^{-2}$. We estimate a stellar mass of $\sim 10^5$ $M_{\odot}$, following a Kroupa mass function. The SMCNOD was probably removed from the SMC disk by tidal stripping, since it is located near the head of the Magellanic Stream, and the literature indicates likely recent LMC-SMC encounters. This scenario is supported by the lack of significant HI gas. Other potential scenarios for the SMCNOD origin are a transient over-density within the SMC tidal radius or a primordial SMC satellite in advanced stage of disruption.